Samkaleen Sabhyata Aur Naari Ka Mehtva: Exploring the Significance of Contemporary Culture and Women's Role (Journal of Advances and Scholarly Researches in Allied Education, 2012)
^^ dkO;s’kq ukVdae~ jE;e~ ^^ dg djlaLd`rkpk;ksZa us vkSj ^^ ukVd thou dh vuqd`fr gS^^ ¼Mªkek bZt bfeV’ku vkWQykbQ½ dgdj vkaXl leh{kdksa us bl n`’;kRed lkfgR;d fo/kk vkSj thou ds laca/k dh?kfu"Brk dks n`